Peran Hukum Dalam Lingkungan Masyarakat - Tamaulina Br. Sembiring; Muhammad Nabiel Arraihan; Muhammad Rafiq; Hafiz Ihsan Lubis; Dedi Ahmad; Deio Valentino Sirait (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This journal examines the role of law in forming and maintaining a harmonious societal environment. The background to this research is based on the increasing complexity of social problems that have legal implications, requiring a deeper understanding of the effectiveness and challenges of implementing law in society. This research aims to analyze how law plays a role in resolving conflicts, protecting citizens' rights, and encouraging sustainable development at the community level. The research method used is qualitative with a case study approach in [specify research location], involving in-depth interviews with residents, law enforcement officials and community leaders. The main findings show that [mention the main findings briefly, for example: legal accessibility is still limited, community participation in law enforcement is still low, or there is a gap between written law and practice in the field]. The implications of this research highlight the need for increased access to justice, more active community participation in the legal process, and legal reform that is responsive to community needs. It is hoped that the results of this research can contribute to the development of legal policies that are more effective and fair in the context of the community environment.